2021
DOI: 10.3389/fonc.2021.650394
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Sorafenib, Camrelizumab, Transcatheter Arterial Chemoembolization, and Stereotactic Body Radiation Therapy as a Novel Downstaging Strategy in Advanced Hepatocellular Carcinoma With Portal Vein Tumor Thrombus: A Case Series Study

Abstract: Background and AimAlthough the treatment effect and availability of therapeutic options for advanced hepatocellular carcinoma (HCC) are limited, the downstaging strategy may improve patient prognosis. This study aimed to investigate the potential of combination therapy as a downstaging strategy for treating advanced HCC with portal vein tumor thrombus (PVTT).MethodsThis retrospective case series included patients having advanced HCC with PVTT, who received the combination therapy of sorafenib, camrelizumab, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
0
18
1
Order By: Relevance
“…In terms of the safety findings, previous studies of patients with intermediate to advanced HCC treated with PD-1 inhibitor plus TACE indicated that the most common adverse events included fever, skin reactions, fatigue, vomiting, hypertension, diarrhea, thrombocytopenia, elevated AST, elevated ALT, asthenia, decreased appetite, rash, and pruritus ( 12 , 28 ). Consistent with previous studies, we found that the incidence of total AEs was 90.1%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the safety findings, previous studies of patients with intermediate to advanced HCC treated with PD-1 inhibitor plus TACE indicated that the most common adverse events included fever, skin reactions, fatigue, vomiting, hypertension, diarrhea, thrombocytopenia, elevated AST, elevated ALT, asthenia, decreased appetite, rash, and pruritus ( 12 , 28 ). Consistent with previous studies, we found that the incidence of total AEs was 90.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Camrelizumab, a PD-1 inhibitor, was independently developed by Jiangsu Hengrui Pharmaceuticals Co., Ltd. in China and has recently been approved by the Chinese Food and Drug Administration (CFDA) to treat hepatocellular carcinoma. A few studies have exhibited the efficacy of camrelizumab in patients with advanced HCC (12)(13)(14). For instance, a study disclosed that a combination of camrelizumab with sorafenib, TACE, and radiotherapy in treating advanced HCC patients with portal vein tumor thrombus achieved a median PFS of 15.7 months and a 1year OS of 83.3% (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Huang et coll. [ 105 ] published a case series including 13 advanced HCC patients with portal vein tumour thrombosis receiving the combination therapy of sorafenib, camrelizumab, transcatheter arterial chemoembolisation and stereotactic body radiation therapy, showing macrovascular invasion regression in 33% of cases. Responder patients underwent hepatectomy.…”
Section: Upper Limits For Downstaging?mentioning
confidence: 99%
“…We previously reported that combined treatment with sorafenib, camrelizumab, TACE, and stereotactic body radiation therapy (SBRT) downstaged advanced HCC with PVTT [ 7 ]. A mean progression-free survival (PFS) of 15.7 months was reported, with an overall response rate reaching 41.7%.…”
Section: Introductionmentioning
confidence: 99%